Modernist Ideas and Local Reception: The company towns of Piazzola sul Brenta and Borgonyà, 1895–1930. (31st October 2016) - Visentin, Francesco
Abstract: Utopianism, paternalism and the myth of progress were the ideological foundations underpinning company towns. These communities, which sprang up towards the end of the nineteenth century, were dependent on a single company for all or most of the functions and services necessary for town life. This article explores aspects of company town life as variously implemented and received depending on cultural and geographical contexts. In particular, this article examines the emergence of two company towns established during the same period but in two distinct geographical contexts: Piazzola sul Brenta in the Veneto (Italy) and Borgonyà in Catalonia (Spain). While development of these two company towns relied on the same ideals of social and technological progress, the visions of their respective companies, their locations and broader topographical circumstances differed significantly. These new towns are examined through key factors reflecting their owners' and planners' faith in social and technological progress, such as the harnessing of water power, the construction of railways and moral paternalism. These features are analysed by reflecting on the meaning of space in specific contexts. Piazzola sul Brenta and Borgonyà were experimental spaces that their designers and owners used to achieve ephemeral social, political and cultural goals, allowing me to examine both the ways and the spaces in which knowledge and ideas were received, and how different types of knowledge and ideas were transformed and realized.